Development of Trypanosoma congolense, T. vivax and T. brucei in the skin reaction induced in goats by infected Glossina morsitans centralis: A light and electron microscopical study - Dwinger, R.H.; Murray, M. (1988)
Examines the development and the ultrastructural and histological distribution of Trypanosoma congolense, T Vivax and T brucei in the skin of goats in Kenya, after the animals were bitten by infected Glossina morsitans centralis.